Sex hormones and n -3 fatty acid metabolism - Childs, Caroline E. (Proceedings of the Nutrition Society, 2020)
α-Linolenic acid (ALA) is an n -3 fatty acid found in plant-derived foods such as linseeds and linseed oil. Mammals can convert this essential fatty acid into longer-chain fatty acids including EPA, docosapentaenoic acid (DPA) and DHA. Women demonstrate greater increases in the EPA status after ALA supplementation than men, and a growing body of animal model research identifies mechanisms by which sex hormones such as oestrogen and progesterone interact with the synthesis of EPA and DHA. Alternatively, EPA, DPA and DHA can be consumed directly, with oily fish being a rich dietary source of these nutrients. However, current National Diet and Nutrition Data reveals a median oily fish intake of 0 g daily across all age ranges and in both sexes. As longer-chain n -3 fatty acids have a crucial role in fetal and neonatal brain development, advice to consume dietary ALA could prove to be a pragmatic and acceptable alternative to advice to consume fish during pregnancy, if benefits upon tissue composition and functional outcomes can be demonstrated. Further research is required to understand the effects of increasing dietary ALA during pregnancy, and will need to simultaneously address conflicts with current dietary advice to only eat ‘small amounts’ of vegetable oils during pregnancy. Improving our understanding of sex-specific differences in fatty acid metabolism and interactions with pregnancy has the potential to inform both personalised nutrition advice and public health policy.